Property Office Management Digitalization for a Government – Owned and Controlled Corporation - Tingson, Noli T.; Pomperada, Jake R (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
The POMD is a web-based and mobile-responsive application developed to support the asset and property management functions of the Property/Procurement/Building and Transport Maintenance Section (PPBTMS) of SRA. The system enables streamlined, real-time tracking and monitoring of fixed assets, including office equipment, laboratory tools, vehicles, and furniture. It features modules for asset registration, maintenance scheduling, depreciation tracking, and inventory reporting compliant with Commission on Audit (COA) requirements.